2021
DOI: 10.3390/polym13244368
|View full text |Cite
|
Sign up to set email alerts
|

Collagen-Based Nanofibers for Skin Regeneration and Wound Dressing Applications

Abstract: Skin regeneration after an injury is very vital, but this process can be impeded by several factors. Regenerative medicine is a developing biomedical field with the potential to decrease the need for an organ transplant. Wound management is challenging, particularly for chronic injuries, despite the availability of various types of wound dressing scaffolds in the market. Some of the wound dressings that are in clinical practice have various drawbacks such as poor antibacterial and antioxidant efficacy, poor me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
41
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 86 publications
(44 citation statements)
references
References 131 publications
2
41
0
1
Order By: Relevance
“…As shown, the porosity of the NFs was recorded in the range 73.5–79.6%, where the porosity decreased by incorporation of nCeO 2 and CEO. This was reported in previous studies, which observed that the incorporated bioactive agents into the polymer-based NFs decreased their porosity compared to the non-loaded NFs [ 58 ]. According to previous studies, engineered membranes with 60–90% porosity could be suitable for tissue regeneration where such a porosity range is ideal to facilitate cell penetration and proliferation at their structure [ 2 ].…”
Section: Resultssupporting
confidence: 80%
“…As shown, the porosity of the NFs was recorded in the range 73.5–79.6%, where the porosity decreased by incorporation of nCeO 2 and CEO. This was reported in previous studies, which observed that the incorporated bioactive agents into the polymer-based NFs decreased their porosity compared to the non-loaded NFs [ 58 ]. According to previous studies, engineered membranes with 60–90% porosity could be suitable for tissue regeneration where such a porosity range is ideal to facilitate cell penetration and proliferation at their structure [ 2 ].…”
Section: Resultssupporting
confidence: 80%
“…GF-loaded electrospun fibers can be achieved by incorporating GFs into the polymeric nanofibers 118 or conjugating them onto the surface. 119 The difference in the GF loading strategies determines a variation in GF release profiles. There was a novel approach proposed by Kulkarni et al in 2014.…”
Section: Growth Factorsmentioning
confidence: 99%
“…Electrospinning is a popular technique to produce nanofibers with controlled‐release GFs. GF‐loaded electrospun fibers can be achieved by incorporating GFs into the polymeric nanofibers 118 or conjugating them onto the surface 119 . The difference in the GF loading strategies determines a variation in GF release profiles.…”
Section: Bioactive Moleculesmentioning
confidence: 99%
“…Two important advantages of electrospun nanofibrous scaffolds are their large available surface area, efficient functionalization, and the possibility of formulating them from a broad variety of natural and synthetic polymers [ 79 , 80 ]. Other benefits of electrospun nanofibers that can contribute to skin regeneration and wound healing applications include high porosity, small diameter, gas permeation, and narrow diameter distribution [ 81 , 82 ]. Some researchers have reported the pre-clinical outcomes of gellan gum-based nanofibers for the treatment of wounds.…”
Section: Gellan Gum-based Wound Dressingsmentioning
confidence: 99%